Detection of lung dysfunction using ventilation and perfusion SPECT in a mouse model of chronic cigarette smoke exposure - Jobse, Brian N; Rhem, Rod G; Wang, Iris Q; Counter, William B; Stämpfli, Martin R; Labiris, N Renée (The Journal of nuclear medicine (1978), 2013)
Chronic obstructive pulmonary disease is a leading cause of morbidity and mortality worldwide. Exposure to cigarette smoke (CS) is a major risk factor for developing this chronic airflow impairment, but the early progression of disease is not well defined or understood. Ventilation/perfusion (V/Q) SPECT provides a noninvasive assessment of lung function to further our current understanding of how CS affects the lung. BALB/c mice were imaged with V/Q SPECT and CT after 8 and 24 wk of whole-body exposure to mainstream CS. Bronchoalveolar lavage was collected and cell differentials produced to determine inflammatory patterns. Histologic lung sections were collected, and a semiautomated quantitative analysis of airspace enlargement was applied to whole histology slices. Exposure to CS induced an inflammatory response that included increases in the numbers of both mononuclear cells and neutrophils. Airspace enlargement was also significantly increased at 8 wk of CS exposure and was still more pronounced at 24 wk. Ventilation and perfusion correlation at the voxel level depicted a significant decrease in matching at 8 wk of CS exposure that was also apparent after 24 wk. The standard deviation (SD) of the log(V/Q) curve, a basic measure of heterogeneity, was increased from 0.44 ± 0.02 in age-matched controls to 0.62 ± 0.05 with CS exposure at 24 wk, indicating an increase in V/Q mismatching between 8 and 24 wk of CS exposure. CT, however, was not capable of discriminating control from CS-exposed animals at either time point, even with greater resolution and respiratory gating. This study demonstrated that, before CT detection of structural changes, V/Q imaging detected changes in gas-exchange potential. This functional impairment corresponded to increased lung inflammation and increased airspace enlargement. In vivo V/Q imaging can detect early changes to the lung caused by CS exposure and thus provides a noninvasive method of longitudinally studying lung dysfunction in preclinical models. In the future, these measures could be applied clinically to study and diagnose the early stages of chronic obstructive pulmonary disease.